POLICY ANALYSIS OF STREET CHILDREN, HOMELESS PEOPLE AND BEGGARSIN BANDAR LAMPUNG CITY - Bambang Utoyo S; Yuyun Fitriani; Sudarman Mersa (Universitas Padjadjaran, 2022)
This research is motivated by the enactment of Regional Regulation No. 03 of 2010 concerning the Guidance of Street Children, Homeless people and Beggars. in the city of Bandar Lampung. The regulation has been in effect since 2010 but until now there are still many street children, homeless people and buskers in Bandar Lampung City. The purpose of this research is to analyze how the implementation of the Regional Regulation No. 03 of 2010. This type of research is descriptive research with a qualitative approach. This research was conducted using the method of collecting through interviews, documentation and observation. The data analysis technique used in this research is data reduction, data presentation and conclusion drawing. The results showed that the implementation of Regional Regulation No. 03 of 2010 concerning the development of street children, homeless people and buskers has not gone well because of the large number of street children and the lack of socialization and counseling carried out by the Social Service regarding the prohibition of giving money on the streets to street children, homeless people. and buskers so that people still carry out these activities. As well as the lack of ability of the Bandar Lampung City Social Service in fostering street children, homeless people and buskers who have been caught in raids.